(untitled) (Journal of Education, Humanities, and Social Research, 2025)
Most of the classic red music works were born at the time of national crisis or the stage of change, and the emotion contained in them can deeply grasp the pain point of the times and show the style of the times. The song On the Songhua River was born in the period of the war of resistance, and it is a classic work of patriotism based on the theme of the September 18th Incident, and it was widely popular among the nationals as soon as it appeared in the world. Although the war is far away now, the spirit of resistance and never outdated patriotic feelings conveyed in the song still has a profound influence on young students in contemporary universities. This paper will explore the educational practice of On the Songhua River in colleges and universities by integrating socialist core values, casting the soul and the spirit of patriotism from the three aspects of the song’s connotation, teaching practice methods, and practical difficulties and solutions.